Household needs among wildfire survivors in the 2017 Northern California wildfires - Mitchell Snyder; Mira Miles; Irva Hertz-Picciotto; Kathryn C Conlon (Environmental Research: Health)
Wildfires are impacting communities globally, with California wildfires often breaking records of size and destructiveness. Knowing how communities are affected by these wildfires is vital to understanding recovery. We sought to identify impacted communities’ post-wildfire needs and characterize how those needs change over time. The WHAT-Now study deployed a survey that was made publicly available for communities affected by the October 2017 Northern California wildfires or the accompanying smoke at beginning approximately four months post-fire with the vast majority completed by nine months post-fire. Among other questions, the survey asked an adult household member to report on their households’ greatest need both one-week post-fire and at the time of survey. A total of 1461 households responded to these questions. Households reported many types of needs, with 154 responses that did not directly name needs but rather described how their households had been affected, which we classified as impacts. Four major themes were identified: physical, health, air, and information, each representing an array of varied specific needs or impacts. Physical needs (e.g. housing, food) were the most common (cited by more than 50% during the fires and about a third at the time of survey). The need for clean air was strong during the fires, but not months later, at the time of survey. In contrast, health needs were reported by a quarter of households during the fires. Needs that were reported at both times were categorized as ‘persistent’, and there were more persistent mental health needs over time compared to other health themes. Understanding the needs and impacts that arise during wildfires, their diversity and duration, and how they change over time is crucial to identifying types of assistance that are most needed during recovery efforts and when they are needed. Results presented here along with other wildfire needs assessments can be utilized to improve disaster preparedness, including for wildfire recovery.